Activation of Fibrinolysis in Guinea-Pig Serum by Bile Acids - Olesen, E. S (Thrombosis and Haemostasis, 1960)
Various bile acids produced fibrinolytic activity in guinea-pig serum under similar conditions as previously established for various anionic polyelectrolytes [Olesen (1959 b,c)].“Tauroglycocholate“ furthermore produced fibrinolytic activity by simple addition to guinea-pig serum.These reactions probably depend on polyanion interactions with active and/or inhibitory components of the fibrinolytic system.The observations suggest that bile acids could be involved in producing fibrinolytic activity in the biliary system.